Longer Cortical Silent Period Length Is Associated to Binge Eating Disorder: An Exploratory Study - Antunes, Luciana C.; Elkfury, Jessica Lorenzzi; Parizotti, Cristiane Schultz; Brietzke, Aline Patrícia; Bandeira, Janete Shatkoski; Torres, Iraci Lucena da Silva; Fregni, Felipe; Caumo, Wolnei (Frontiers in Psychiatry, 2020)
Objectives: i) To compare, among subjects with BED, Obesity, ex-obese and HS- healthy subject, the cortical excitability indexed by TMS measures, such as CSP- cortical silent period (primary outcome), SICI- intracortical inhibition and ICF- intracortical facilitation (secondary outcome). ii) To explore the relationship the CSP and the inhibition response through the Go/No-go paradigm with eating behavior psychopathology measures Methods: 59 women, [BED (n=13), Obese (n=20), ex-obese (n=12) and HC (n=14)]. Assessments: cortical excitability measures (CSP, SICI, ICF), inhibition response task by the Go/No-go paradigm, and instruments to assess the eating psychopathology (Three-Factor Eating Questionnaire, Eating Disorder Examination Questionnaire and Binge Eating Scale). Results: A MANCOVA analysis revealed that the mean of CSP was larger in the BED group compared with other three groups: 24.10% larger than obesity group, 25.98% larger than HC group, and 25.41% larger than ex-obesity subjects group, respectively. Pearson’s correlations evidenced that cortical silent period was positively associated with both eating concern and binge eating scores. Conclusion: The find results demonstrate an up-regulation of intracortical inhibitory in the BED as indicated by a longer CSP.